The Relationship Of Working Posture And Individual Factors With Complaints Of Low Back Pain In Brick-Making Workers In South Jambi In 2020 - Fitria Eka Putri; Lista Oktarina; Rumita Ena Sari; Hubaybah; Adelina Fitri; Fajrina Hidayati; Oka Lesmana (International Journal of Health Engineering and Technology, 2022)
Jambi City 40.5% of diseases are caused by work activities and musculoskeletal complaints, including the 10 largest diseases. Low back pain is a muscelusceletal complaint that is often suffered. This study was conducted to determine the relationship between work posture and individual factors with complaints of low back pain in brick-making workers in the South Jambi District. This type of research was an observasional research with a cross sectional design. The population of this study were all workers in the small brick-making industry in South Jambi District, Jambi City. The number of samples was 66 workers who were taken by proportional random sampling. The data obtained were analyzed with the chi-square test. Workers who experience work postures with a RULA value of 7 must implement changes as quickly as possible as many as 10 workers (15.2%), workers who experience work postures with a RULA value of 5-6 must carry out investigations and immediate improvements as many as 17 workers (25.8) , Workers who have a work posture with a RULA value of 3-4 may need a change of 21 workers (31.8%), Workers who have a work posture with a RULA value of 1-2 good work postures and can be accepted as many as 18 workers (27.3% ). Workers as many as 50 workers (75.8%) and 17 people (25 , 8%) have an abnormal BMI and are at risk. The factors associated with pain relief under work posture obtained p-value: 0.054 (˃0.05) with a PR value: 1.768 (95% CI: 0.961-3.253), age obtained p- value: 0.014 (< 0, 05) with PR value: 2,240 (95% CI: 1,059-4,738) and BMI obtained p-value: 0,322 (˃0,05) with PR value: 1,237 (95% CI: 0835-1,826). There were relationship between work posture and complaints of low back pain in workers, but there is no close relationship between BMI and complaints of low back pain in brick-making workers in The South Jambi District.